KEGIATAN JUDI ONLINE DIKALANGAN PELAJAR DAN MAHASISWA DI KOTA PEKANBARU (Studi Tentang Judi Online Pada Lima Warnet di Kelurahan Maharatu, Kecamatan Marpoyan Damai) - Syafrul Hardiansyah; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Information media such as the internet are very influential among the people at present, a wide range of information can be found on the internet. The ease of accessing the internet makes users increasingly free to get whatever information, including misuse of the internet. Online gambling is a great example of the misuse of the internet continues to grow as the development of the times, crime in the form of gambling is so casily found on the internet. All people can benefit from the game are gambling that to gain an advantage in the form of money. A lack of laws regulating online gambling is about the increasing number of players making from various backgrounds including students. Gambling game online is the development of advances about technology applied to electronic medi or gambling internet, as is online gambling the players that normally play in person or face-to-face has now switched to play online. Players who normally play for stealth now can play outrigth freely without any fear of legal officers. This reseach aims to look at how the online gambling player activities among students, as well as howthey choose the type of ofline gambling games. Gambling game online in this study such as, ball gambling, poker gambling, and dominoes 99 (ciu-ciu). Keywords : Online gambling, among the students